Transient and Steady-State Properties of Drosophila Sensory Neurons Coding Noxious Cold Temperature - Maksymchuk, Natalia; Sakurai, Akira; Cox, Daniel N.; Cymbalyuk, Gennady (Frontiers in Cellular Neuroscience, 2022)
Coding noxious cold signals, such as the magnitude and rate of temperature change, plays an essential role in the survival of organisms. We combined electrophysiological and computational neuroscience methods to investigate the neural dynamics of Drosophila larva cold-sensing Class III (CIII) neurons. In response to a fast temperature change (-2 to -6 °C/s) from room temperature to noxious cold, the CIII neurons exhibited a pronounced peak of spiking rate with subsequent relaxation to a steady-state spiking. The magnitude of the peak was higher for a higher rate of temperature decrease, while slow temperature decrease (-0.1 °C/s) evoked no distinct peak of the spiking rate. The rate of the steady-state spiking depended on the magnitude of the final temperature and was higher at lower temperatures. For each neuron, we characterized this dependence by estimating the temperature of the half-maximal activation by curve-fitting neuron’s spiking rate responses to a Boltzmann function. We found that neurons had a temperature of the half-maximal activation distributed over a wide temperature range. We also found that CIII neurons responded to the temperature decrease rather than increase. There was a significant difference in spiking activity between fast and slow temperature return from noxious cold to room temperature: the CIII neurons usually stopped activity abruptly in the case of the fast return and continued spiking for some time in the case of the slow return. We developed a biophysical model of CIII neurons using a generalized description of TRP current kinetics with temperature-dependent activation and Ca2+-dependent inactivation. This model recapitulated the key features of the spiking rate responses found in experiments, and suggest mechanisms explaining the transient and steady-state activity of the CIII neurons at different cold temperature magnitudes and in response to different rates of temperature decrease and increase. We conclude that CIII neurons could encode at least three types of cold sensory information: rate of temperature decrease by a peak of firing rate, the magnitude of cold temperature by a rate of steady spiking activity, and direction of temperature change by spiking activity augmentation or suppression corresponding to temperature decrease and increase, respectively.